Oral health status among lorry drivers in Hyderabad city – A cross sectional study. - Loka, Suraj Reddy; Doshi, Dolar; Kulkarni, Suhas; Reddy, Loka Sudarshan; Baldava, Pavan; Dasari, Tejaswini (Work, 2024)
BACKGROUND: Lorry drivers work tirelessly behind the wheels, commuting from one place to another without regular and adequate food, rest and sleep. These people often have odd working hours, long work shifts with frequent changes to their work schedule. In addition, they work in unfavorable climate conditions and face variety of problems like traffic congestions, vehicle fumes, vibrations and poor conditions of roads. Due to this hectic schedule they commonly fall prey to unhealthy lifestyle habits in the form of alcohol consumption, smoking, tobacco chewing etc. mainly to relieve stress. Considering all these factors, lorry drivers form a potential high risk group for oral problems. OBJECTIVE: The present study aimed to assess the oral health status among lorry drivers in Hyderabad city. METHODS: A total of 611 subjects constituted the study population. Data collection included demographic details and assessment of dentition status, periodontal status and presence of oro-mucosal lesions using modified World Health Organization (WHO) Oral Health Assessment form, 2013. The data was analyzed using Statistical Package for Social Sciences (SPSS) package version 21.0. Descriptive statistics were carried out for the demographic variables. Chi square test, Mann Whitney U test, Analysis of Variance and regression analysis determined the association and compared the mean scores based on variables. p < 0.05 was considered statistically significant. RESULTS: The mean dental caries experience was significantly higher among subjects above 40 years (3.11±2.49; p < 0.01*), and those with high school education (3.91±2.75; p < 0.005*). Likewise, a significant difference in the mean number of teeth with bleeding and pockets was observed based on age (p < 0.01*) and education (p < 0.01*). Subjects above 40 years and those with primary school education had significantly higher mean scores for loss of attachment (p < 0.001*). Oral submucous fibrosis on the buccal mucosa was the most commonly seen oral lesion. Regression analysis revealed subjects above 40 years, with high school education and a history of tobacco and alcohol consumption to have higher odds for DMFT, poor periodontal health and oral mucosal lesions. CONCLUSIONS: The study revealed that lorry drivers had a high prevalence of dental caries, poor periodontal status and oro-mucosal lesions. Therefore, it creates an alarming need to focus on these high risk groups with special emphasis on primary oral health care programs to prevent accumulation of health care demands among them.